Inefficient Placental Virus Replication and Absence of Neonatal Cell-Specific Immunity Upon Sars-CoV-2 Infection During Pregnancy - Tallarek, Ann-Christin; Urbschat, Christopher; Fonseca Brito, Luis; Stanelle-Bertram, Stephanie; Krasemann, Susanne; Frascaroli, Giada; Thiele, Kristin; Wieczorek, Agnes; Felber, Nadine; Lütgehetmann, Marc; Markert, Udo R.; Hecher, Kurt; et al. (Frontiers in Immunology, 2021)
Pregnant women have been carefully observed during the COVID-19 pandemic, as the pregnancy-specific immune adaptation is known to increase the risk for infections. Recent evidence indicates that even though most pregnant have a mild or asymptomatic course, a severe course of COVID-19 and a higher risk of progression to diseases have also been described, along with a heightened risk for pregnancy complications. Yet, vertical transmission of the virus is rare and the possibility of placental SARS-CoV-2 infection as a prerequisite for vertical transmission requires further studies. We here assessed the severity of COVID-19 and onset of neonatal infections in an observational study of women infected with SARS-CoV-2 during pregnancy. Our placental analyses showed a paucity of SARS-CoV-2 viral expression ex vivo in term placentae under acute infection and in convalescent pregnant women. Inoculation of placental explants from healthy women with SARS-CoV-2 in vitro revealed inefficient SARS-CoV-2 replication in different types of placental tissues, which provides a rationale for the low ex vivo viral expression. We further detected specific SARS-CoV-2 T cell responses in pregnant women within a few days upon infection, which is undetectable in cord blood. Our present findings confirm that vertical transmission of SARS-CoV-2 is rare, likely due to the inefficient virus replication in placental tissues. Despite the predominantly benign course of infection in most mothers and negligible risk of vertical transmission, continuous vigilance on the consequences of COVID-19 during pregnancy is required, since the maternal immune activation in response to the SARS-CoV2 infection may have long-term consequences for children’s health.